FIRST USE OF ALEMTUZUMAB IN BALO CONCENTRIC SCLEROSIS: A CASE REPORT. Issue 11 (9th October 2013) - William L Brown, J; Jones, Joanne L; Coles, Alasdair J
Abstract : We describe an unsuccessful treatment of Balo concentric sclerosis (BCS), review the current evidence directing therapy, and propose next steps for exploring this rare and commonly fatal condition. Case Report: A 52–year–old left–handed engineer reported three weeks of progressive left leg weakness. Examination revealed pyramidal weakness, hyperreflexia and spasticity in the left leg. An MRI head scan showed concentric sclerosis in the right frontoparietal region (Figure 1A). He was diagnosed with Balo concentric sclerosis (BCS). Sequential courses of oral and intravenous steroids, plasma exchange and pulsed cyclophosphamide failed to slow his decline with spread to the left side of his face and arm after six months (Figure 1B). Given its high efficacy on relapse rate and disability accumulation in relapsing–remitting Multiple Sclerosis we administered a standard protocol of alemtuzumab (Campath–1H). At the time of administration his expanded disability status scale (EDSS) score was 6.5. He experienced no immediate or delayed complications. He continued to accrue clinical and radiological evidence of disease progression at the preceding rate including left hemispheric involvement (Figure 1C). 6 months after alemtuzumab administration he was bedbound, totally dependent and fed via nasogastric tube (EDSS score 9.5); 4 months later he died from aspiration pneumonia, 16 months after his first symptoms. Discussion: This first use of alemtuzumab in Balo's concentric sclerosis produced no therapeutic effect. BCS was previously a pathological diagnosis; the advent of MRI technology revealed lesions comprising rings of demyelination with alternating intact myelin bands throughout the neuroaxis (though most commonly in the brain). Pathologically the intact myelin rings are thought to arise through upregulation of ischaemia–tolerance factors induced by immediately adjacent inflammatory demyelination; the lesion eventually progresses to demyelinate tissue beyond this protected band giving rise to the characteristic concentric appearance. BCS may follow a monophasic, relapsing–remitting or relentlessly progressive course; thus far the scarcity of cases has precluded identifying early features that predict subtype. An asymptomatic case found at post–mortem has also been reported. Determining whether clinical improvement reflects the natural history or a response to immunomodulatory therapy is therefore challenging. Some patients with BCS have improved without treatment or following corticosteroids, plasma exchange, cyclophosphamide, mitoxantrone or combined intravenous immunoglobulin with interferon–beta, giving some support to immunomodulatory treatment avenues. Alemtuzumab, a humanised monoclonal antibody, has shown high efficacy in relapsing–remitting Multiple Sclerosis reducing both the risk of relapse and disability accumulation; but, like other immunotherapies, it has no effect on progressive Multiple Sclerosis. No clinical or radiological improvement followed this first use in BCS. It is hard for the clinician, aware of the inflammatory pathology of Balo's, to withhold immunotherapy, and at least high–dose steroids seem appropriate and in many cases effective. But the rarity of the condition, and its unpredictable natural history, mean there is no robust evidence that immunotherapies alter its long–term course. A practical solution would be a systematic register of cases of Balo's, collecting information on disease course and treatment.